Effect of Digital Mode for Learning Algebraic Formulae among Students with Visual Impairment - Ruth, R. Nagomi; Naomi, G. Victoria (Journal of Cultural Analysis and Social Change, 2025)
Digital technologies propelled Math education rapidly in recent decades. In secondary school math curriculum, algebra is a core topic. There are limited resources for students with visual impairment in the academic field particularly subject like Math that are with symbols, and formulae. With this premise, the study aimed to develop Digital Mode for Algebraic Formulae and study its effectiveness by introducing the Digital Mode to students with visual impairment. The study adopted experimental method involving 53 students with visual impairment. The Digital Mode developed is a web-based tool which conveys meaning of Algebraic Formulae that are visually oriented and thus its reading mode ensures interpretation of formulae. After introduction of Digital Mode for Algebraic Formulae to the visually impaired students, the results showed a significant improvement in learning Algebraic Formulae in this experimental study. Therefore, the study indicated that Digital Mode is efficacious for learning Algebraic Formulae among students with visual impairment.